1992
DOI: 10.1111/j.1469-8137.1992.tb01111.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boron on the growth and mineral economy of some halophytes and non‐halophytes

Abstract: SUMMARYGrowth of halophytes in nutrient solutions with increasing boron concentrations was less reduced than that of some non-halophytes. Boron (B) concentrations occurring in sea water (0350 mol m"^ B) depressed growth of glycophytic plant spec.es strongly, while growth of halophytes did not significantly differ from that under control conditions (Hoagland's nutrient solution containing 0-025 mol m '' B).With increasing boron concentrations m the medium, the total boron concentrations m the shoot tissue incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…The significant decrease in B concentration at saline conditions might be due to either increased pH of soil by addition of NaCl or due to salinity induced stomatal resistance because B uptake is a passive process and influenced by transpiration rate and reduced uptake and translocation in plant (Eraslan et al, 2007). This can be regarded as mechanism of reducing the severity of B toxicity by decreasing B absorption in shoot and stem (Rozema et al, 1992;Grattan et al, 1997). However, accumulation of B differs with growth conditions and crop, e.g., maize and barley did not show interactive response of salt stress and B (Shani and Hanks, 1993) and another study showed that B uptake was increased in Zea mays L. (Bastías et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The significant decrease in B concentration at saline conditions might be due to either increased pH of soil by addition of NaCl or due to salinity induced stomatal resistance because B uptake is a passive process and influenced by transpiration rate and reduced uptake and translocation in plant (Eraslan et al, 2007). This can be regarded as mechanism of reducing the severity of B toxicity by decreasing B absorption in shoot and stem (Rozema et al, 1992;Grattan et al, 1997). However, accumulation of B differs with growth conditions and crop, e.g., maize and barley did not show interactive response of salt stress and B (Shani and Hanks, 1993) and another study showed that B uptake was increased in Zea mays L. (Bastías et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of B in the salt marsh system has been suggested since B concentration in sea water is 15 to 20 times higher than what is considered optimal for nonhalophytes (Rozema et al 1992). Rozema et al (1992) found that halophytes took up less B compared to nonhalophytes, growth in halophytes was not reduced at B concentrations found in sea water (0.35 mol m −3 ), and most species took up less Na with increased B. This study did not include B. frutescens but found a lot of variation between six halophyte species in response to B.…”
Section: No Genotypic Differentiation or Specialization To Salt Levelmentioning
confidence: 99%
“…B is an essential nutrient for normal growth, but the role of B is not completely understood, and the difference between levels that are deficient and levels that are toxic in soils is relatively small for most plants (Rozema et al 1992;Camacho-Cristóbal et al 2008). The importance of B in the salt marsh system has been suggested since B concentration in sea water is 15 to 20 times higher than what is considered optimal for nonhalophytes (Rozema et al 1992). Rozema et al (1992) found that halophytes took up less B compared to nonhalophytes, growth in halophytes was not reduced at B concentrations found in sea water (0.35 mol m −3 ), and most species took up less Na with increased B.…”
Section: No Genotypic Differentiation or Specialization To Salt Levelmentioning
confidence: 99%
“…At the time of planting, the age of seeds was not specified most of the time (Harvey, 1989;Maathuis & Prins, 1990;Rozema et al, 1992;Forbes et al, 1996). Several authors indicated that the seeds had been harvested during the same year (Jefferies et al, 1979;Pons, 1991b;Horner & Bell, 1995;Saker & Kawashity, 1998) or in the previous two or three years (Gagnaire et al, 1975;Flanagan & Jefferies, 1989).…”
Section: B Age Of Seeds and Impact Of This Traitmentioning
confidence: 99%
“…Typical nutritive solutions reported for Plantago are listed in Table III as Hoagland solution (Miao et al, 1991;Rozema et al, 1992;Hoagland & Snijder, 1993), Johnson Solution (Johnson et al, 1957Flanagan & Jefferies, 1989), Lewis and Powers solution (Lewis & Powers, 1941;Smakman & Hofstra, 1982), Steiner solution (Steiner, 1968;Lotz et al, 1990) and other nutrient solutions (Cooper & Etherington, 1974;Cooper, 1976).…”
Section: G Solid Substrates and Additional Nutritive Solutionsmentioning
confidence: 99%